SOCIAL PRACTICES OF LITERARY READING IN SCHOOL AND NON-SCHOOL SPACES - Mello, Cláudio (2022)
This article presents specificities of the approach to literature in school and non-school spaces in a dialogic perspective in which reading is considered an authentic social practice. The objective is to contribute to resizing objectives and decision-making about theoretical-methodological assumptions both in one and the other space, in favor of an educational action that preserves the appreciation for literature, at the same time that takes advantage of opportunities to promote the formation of an increasingly sensitive, autonomous and critical reader.